Management of refractory hypoxemia using recruitment maneuvers and rescue therapies: A comprehensive review - Bajon, Félix; Gauthier, Vincent (Frontiers in Veterinary Science, 2023)
Refractory hypoxemia in patients with acute respiratory distress syndrome treated with mechanical ventilation is one of the most challenging conditions in human and veterinary intensive care units. When a conventional lung protective approach fails to restore adequate oxygenation to the patient, the use of recruitment maneuvers and positive end-expiratory pressure to maximize alveolar recruitment, improve gas exchange and respiratory mechanics, while reducing the risk of ventilator-induced lung injury has been suggested in people as the open lung approach. Although the proposed physiological rationale of opening and keeping open previously collapsed or obstructed airways is sound, the technique for doing so, as well as the potential benefits regarding patient outcome are highly controversial in light of recent randomized controlled trials. Moreover, a variety of alternative therapies that provide even less robust evidence have been investigated, including prone positioning, neuromuscular blockade, inhaled pulmonary vasodilators, extracorporeal membrane oxygenation, and unconventional ventilatory modes such as airway pressure release ventilation. With the exception of prone positioning, these modalities are limited by their own balance of risks and benefits, which can be significantly influenced by the practitioner's experience. This review explores the rationale, evidence, advantages and disadvantages of each of these therapies as well as available methods to identify suitable candidates for recruitment maneuvers, with a summary on their application in veterinary medicine. Undoubtedly, the heterogeneous and evolving nature of acute respiratory distress syndrome and individual lung phenotypes call for a personalized approach using new non-invasive bedside assessment tools, such as electrical impedance tomography, lung ultrasound, and the recruitment-to-inflation ratio to assess lung recruitability. Data available in human medicine provide valuable insights that could, and should, be used to improve the management of veterinary patients with severe respiratory failure with respect to their intrinsic anatomy and physiology.